404 Vermont dairy calf management practices and opportunities. (7th December 2018) - Smith, J; Cosentino, M
Abstract: Where calf management practices fall short of best practices, an opportunity for improved outcomes may exist. A multi-modal survey was conducted of Vermont dairy farmers in 2014 to collect data on calving practices, feeding of neonatal and pre-weaned calves, calf housing, and calf health. Ninety surveys were completed out of 179 mail-in surveys, telephone or face-to-face interviews. A total of 886 dairy farms were operating at the time. Results reported have a 95% confidence interval +/- 10%. Colostrum feeding protocols for heifer and bull calves did not differ on 80% of farms, but the reason for differences was not determined. About half of farms did not assess quality of colostrum and about 90% did not evaluate success of passive transfer. Non-saleable transition or treated milk was fed on more than half of farms and over a third reported feeding either medicated or non-medicated milk replacer. Medicated milk replacer was fed to bull calves on 8 farms. Antibiotic residues in bull calves were identified as a concern by about 10% of respondents. Farm antibiotic use included a few reports of gentamicin, phenylbutazone, tilmicosin, tylosin, neomycin, and dihydrostreptimycin. The most common antibiotics in use were ceftiofur (42%), flunixin (42%), penicillin (37%), ampicillin (31%), oxytetracycline (27%), and florfenicol (24% of farms). Barn cats were present as a means of pest control in calf facilities of about 70% of farms. The most commonly used vaccines targeted respiratory viruses, leptospirosis, and rabies. Only 3 of 24 respondents wanted more information on drug stewardship and drug residue avoidance. Vaccinations and nutrition were identified by 18 of 24 respondents as areas where more information or training would be desired. About half (of the 24 respondents wanting additional information) were interested in the topics of calving management and ventilation of calf housing.